1,2,4-oxadiazole: A Brief Review from the Literature About the Synthesis and Pharmacological Applications - ROSA, Mauricio Ferreira da; MORCELLI, Ana Carolina Teixeira; LOBO, Viviane da Silva (Visão Acadêmica, 2015)
This work includes a brief discussion about the most used methods for the synthesis of 1,2,4-oxadiazole ring, highlighting their advantages and disadvantages. It was also realized a search in the literature about the main functions of this group, its action in the treatment of diseases, the tests made for the confirmation of the pharmacological actions and the results obtained.